Uma análise sobre a relação entre o retorno de empresas brasileiras e os componentes do ciclo de conversão de caixa - Sousa, Thiago Ferreira de (2016)
Literature devoted to study the working capital and profitability relation points out that the cash conversion cycle and its components are linked to companies’ results. This empirical dissertation aims to estimate this relation for Brazil, using a self-constructed database, composed mostly by closely held and privately owned companies. Following Lazaridis and Tryfonidis (2006) and Gill, Biger and Mathur (2010), and applying a fixed effect methodology, the results confirm the well documented inverse relation between operating profit rate and cash conversion cycle present in the literature. A sectoral analysis is conducted and indicates that industry, commerce and services confirm these patterns. Agriculture and energy, however, do not present significant results, which, by its turn, indicates that profitability in these sectors has a different approach when compared to the others. Futures researches should focus on understanding these differences.